2006
DOI: 10.1080/13697130500487224
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms in women treated for breast cancer: the prevalence and severity of symptoms and their perceived effects on quality of life

Abstract: The majority of women receiving treatment for breast cancer report menopausal symptoms, which negatively correlate, not only with their own, but also with their partner's quality of life. Most women experiencing hot flushes are not receiving treatment due to lack of both awareness and confidence in the existing treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
5
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 36 publications
15
141
5
10
Order By: Relevance
“…However, the mechanism of venlafaxine's effects on hot flashes remains unclear. That a 50% or more decrease in physiological hot flashes was associated with improved secondary outcomes supports the existence of a symptom cluster or menopausal syndrome as proposed by others [5,[45][46][47]. Because secondary outcomes were linked to physiological hot flashes, these improvements are not an artifact of positive reporting bias.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, the mechanism of venlafaxine's effects on hot flashes remains unclear. That a 50% or more decrease in physiological hot flashes was associated with improved secondary outcomes supports the existence of a symptom cluster or menopausal syndrome as proposed by others [5,[45][46][47]. Because secondary outcomes were linked to physiological hot flashes, these improvements are not an artifact of positive reporting bias.…”
Section: Discussionmentioning
confidence: 48%
“…Frequent, severe, and bothersome hot flashes are well documented in breast cancer survivors [1][2][3][4][5]. Approximately 65% of survivors experience hot flashes, with 59% rating the symptom as severe and 44% rating the symptom as extremely bothersome.…”
Section: Introductionmentioning
confidence: 99%
“…), compared them against placebo or other SSRIs, and evaluated vasomotor symptoms (daily hot flash frequency or improvement in vasomotor scores). We specifically excluded studies that enrolled cancer patients and patients receiving selective estrogen receptor modulators (SERMs) because hot flashes and night sweats are common complaints (up to 80 %) of patients receiving tamoxifen for breast cancer, [14][15][16] women taking hormonal replacement therapy and patients with diagnoses of depression.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…16 SSRIs in these women may also speed the metabolism of tamoxifen to inactive metabolites, possibly reducing the severity of side effects, including hot flashes. 39 Therefore, our findings relate to women suffering from natural peri-and post-menopausal symptoms.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…In the Arimidex, Tamoxifen, Alone or in Combination trial, vaginal dryness was observed in 16.3% and dyspareunia was observed in 17.8% of anastrozole-treated patients, but in only 8.4% and 7.5% of tamoxifen-treated patients, respectively [2]. As AIs are used more frequently in the growing population of postmenopausal women with hormone receptor-positive breast cancer, this serious complication of therapy that dramatically affects quality of life will become more common [3].…”
Section: Introductionmentioning
confidence: 99%